Aristotle and the virtues - Curzer, Howard J. (Oxford : Oxford University Press, 2012)
Howard J. Curzer presents a fresh new reading of Aristotle's 'Nicomachean Ethics', which brings each of the virtues alive. He argues that justice and friendship are symbiotic in Aristotle's view; reveals how virtue ethics is not only about being good but about becoming good; and describes Aristotle's quest to determine happiness.
Description based on online resource; title from PDF title page (viewed on Apr. 19, 2012).
Includes bibliographical references and index.
Keywords: Aristotle